The Aspergillus flavus fluP-associated metabolite promotes sclerotial production. Issue 10 (October 2016) - Chang, Perng-Kuang; Scharfenstein, Leslie L.; Ehrlich, Kenneth C.; Diana Di Mavungu, José
Abstract: Aspergillus flavus is able to synthesize a variety of polyketide-derived secondary metabolites including the hepatocarcinogen, aflatoxin B1 . The fungus reproduces and disseminates predominantly by production of conidia. It also produces hardened mycelial aggregates called sclerotia that are used to cope with unfavourable growth environments. In the present study, we examined the role of A. flavus fluP, the backbone polyketide synthase gene of secondary metabolite gene cluster 41, on fungal development. The A. flavus CA14 fluP deletion mutant (AfΔfluP) grew and accumulated aflatoxin normally but produced a lower amount of sclerotia than the parental strain. This was also true for the Aspergillus parasiticus BN9 fluP deletion mutant (ApΔfluP). The A. flavus fluP gene was positively regulated by developmental regulators of VeA and VelB but not by the global regulator of secondary metabolism, LaeA. Overexpression of fluP in AfΔfluP (OEfluP) elevated its ability to produce sclerotia compared to that of the parental strain. Coculture of OEfluP with CA14, AfΔfluP, ApΔfluP, or an A. flavus pptA deletion mutant incapable of producing functional polyketide synthases also allowed increased sclerotial production of the respective strains at edges where colonies made contact. Acetone extracts of OEfluP but not of AfΔfluP exhibited the same effect in promoting sclerotial production of AfΔfluP. These results suggest that FluP polyketide synthase is involved in the synthesis of a diffusible metabolite that could serve as a signal molecule to regulate sclerotiogenesis. Highlights: The Aspergillus flavus metabolite gene cluster 41 contains a polyketide synthase gene. The pks gene is the orthologue of the fluP gene reported for Aspergillus parasiticus . The fluP mutant accumulates aflatoxin normally but decreases sclerotial production. The fluP -associated metabolite is diffusible and able to promote sclerotiogenesis.